Efektivitas Peer Assessment dalam Menilai Kemampuan Kinerja Siswa pada Kegiatan Praktikum Biologi - Siti Sriyati; Asep Permana; Arini Arini; Mia Purnamasari (Universitas Sebelas Maret, 2016)
This study aimed to describe the effectiveness of peer assessment in assessing the performance ability of students in Biology lab activities. Method in this research is descriptive method. The research was conduct in three schools : two schools at the junior high school and one school at the senior high school level. The material of lab activities are characteristics of living things and the pollution of soil in Junior high school and water pollution in senior high school. In three class sample application of peer assessment conducted through mutual judging between friends in one group. Everyone in the group assessed by at least two of the group's friends. The assessment was conducted after the practicum process is finish. The instrument used in this study of performance observation sheet that is used when the implementation of peer assessment. To see the effectiveness of student assessment results, the assessment carried out by teachers. The results showed that the assessment of the student is larger than teacher assessment in Senior High School. Similarity assessment conducted through peer assessment of students with teacher assessment results in practical characteristics of living beings is 44 % , the material soil pollution 44 % and the material water pollution by 45 %.Keywords: effectiveness , peer assessment, student performance , teacher assessment , lab